2021
DOI: 10.1016/j.ijid.2021.04.057
|View full text |Cite
|
Sign up to set email alerts
|

Clinical usefulness of metagenomic next-generation sequencing for the diagnosis of central nervous system infection in people living with HIV

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 31 publications
(33 reference statements)
1
20
1
Order By: Relevance
“…The culture method is often regarded as the gold standard of fungal infection, but most fungi should be cultured a relative long time, some of them even need a culture time as long as one month. The histopathological diagnosis is an invasive examination, whose sensitivity and specificity largely depend on the experience of pathologists, and there often exists a certain misdiagnosis rate[ 19 , 20 ]. This study showed that the positive rate of the fungal CNS infection detected by mNGS was 17/27(62.96%), while that of the conventional methods was only 12/17(44.4%).…”
Section: Discussionmentioning
confidence: 99%
“…The culture method is often regarded as the gold standard of fungal infection, but most fungi should be cultured a relative long time, some of them even need a culture time as long as one month. The histopathological diagnosis is an invasive examination, whose sensitivity and specificity largely depend on the experience of pathologists, and there often exists a certain misdiagnosis rate[ 19 , 20 ]. This study showed that the positive rate of the fungal CNS infection detected by mNGS was 17/27(62.96%), while that of the conventional methods was only 12/17(44.4%).…”
Section: Discussionmentioning
confidence: 99%
“…Previous study showed that multiple pathogens were identified by NGS in CSF from more than 15.9% (14/88) of HIV-infected patients who were suspected to have CNS infection with negative result by conventional tests. This indicated that multipathogenic CNS infections are not uncommon in people living with HIV and NGS is capable to identify multiple pathogens in a single test in an unbiased manner (1). Although there is one previous report about the application of NGS in the identification of streptococcus suis septicemia in a patient whose blood bacterial cultures results were negative (14), its application in diagnosing streptococcus suis meningitis in HIV-infected patients with cryptococcal meningitis history has never been addressed until now.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to patients with monomicrobial meningitis, patients infected with multiple types of meningitis are more difficult to be diagnosed (1). However, a fast and accurate diagnosis of the pathogens causing the meningitis is challenging because of the limitations of current conventional tests (2).…”
Section: Introductionmentioning
confidence: 99%
“…149 Sensitivity of mNGS has been compromised in few studies, compared to amplification-based assay due to the low viral loads in the specimen which is a common problem. 143,150 A recent study was conducted to counter this problem by enhanced the laboratory technique using hybrid capture (HC) of viral nucleic acids and methylated DNA depletion (MDD) to improve the sequencing analytical sensitivity. As the results, HC able to increase the viral read recovery in almost universally.…”
Section: Next Generation Sequencingmentioning
confidence: 99%